1971
DOI: 10.1029/wr007i003p00591
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Solids‐Discharge Relationships: 2. Applications to Field Data

Abstract: Six mixing models and a number of equations derived from them have been proposed for some possible dissolved solids‐discharge relationships in streams. The equations can be put in a form suitable for statistical analysis by digital computer. In actual application, however, a major problem arises in determining which equation or model is most applicable because the data tend to fit two or more equations equally well. A particular difficulty is encountered in deciding whether a constant component of dissolved so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

1976
1976
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 4 publications
1
41
0
2
Order By: Relevance
“…Typical concentration-discharge analyses have centered on mixing models of different source waters (e.g. event and pre-event water; old and new water; or soil water, groundwater and precipitation) inferred from the shape of the concentration-discharge relationship for different solutes (Johnson et al, 1969;Hall, 1970Hall, , 1971. In other studies, researchers have inferred the relative timing of mixing from hysteresis loops observed in concentration-discharge plots (Evans and Davies, 1998;Evans et al, 1999;House and Warwick, 1998;Hornberger et al, 2001;Chanat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Typical concentration-discharge analyses have centered on mixing models of different source waters (e.g. event and pre-event water; old and new water; or soil water, groundwater and precipitation) inferred from the shape of the concentration-discharge relationship for different solutes (Johnson et al, 1969;Hall, 1970Hall, , 1971. In other studies, researchers have inferred the relative timing of mixing from hysteresis loops observed in concentration-discharge plots (Evans and Davies, 1998;Evans et al, 1999;House and Warwick, 1998;Hornberger et al, 2001;Chanat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Within the overall loop a secondary loop system is evident; this is most likely caused by individual storms, a phenomenon which forms hysteresis (Hall 1971).…”
Section: Hysteresis In Relationshipsmentioning
confidence: 99%
“…Various adaptations of this latter model have been investigated (Hall, 1970(Hall, , 1971, and estimates ot me various contributions to streamtlow chemical quality from distinct flow components (storm runoff and baseflow) can be evaluated (Steele, 1968). With either of the above models, nonlinear relations can be approximated by use of segmented linear functions.…”
Section: Approachmentioning
confidence: 99%